Métodos de control y seguridad del archivo físico y digital de la cooperativa de ahorro y crédito los Chasquis ubicada en Lasso provincia Cotopaxi. - Alvarado Robalino, Alejandra Paola (2014)
This research has as objective to develop control and security methods of the physical and digital archive which help to minimize de processing time of documents, taking into account the steps, simultaneously provides the knowledge of archives administration, document management, and file officials administration from the ChasquisSavings and Credit Cooperative. These issues are very important at the moment of the reception, opening, classification and distribution of documents. The methodology used in this proposal is descriptive, based on exhaustive research, which allowed reaching a theoretical construction and an archival display problem. In this research, we obtained excellent and positive results in the ChasquisSavings and Credit Cooperative. Through the surveys which were applied to the administrative staff and the interview used with the general manager of the institution, it was possible to evidence the existing problems within the Cooperative’s documentary organization. Based on the obtained results, it was developed the Control and Security Methods of the Physical and Digital Archive. This work was produced with all procedures for the correct classification, documental transfer from archive. In order to prevent loss and damage of the documents, it is important to keep the documents in good conditions; therefore an adequate furniture and physical space are necessary to protect the documentary because each document generated in each department will serve as a historical heritage of the institution.